“A Treasure for the Poor”: The Contents of the Temple Treasures according to 2 Macc 3:10 in Light of the Biblical and Ancient Jewish and Christian Traditions - Martins, Francisco (Harvard theological review, 2020)
The attack of Heliodorus on the temple in 2 Macc 3 is the first of a series of events occupying the narrative core of the book. In the first act of the story, a dispute arises over the actual contents of the temple treasury, with the high priest Onias claiming that they are “deposits of widows and orphans” (3:10). This essay focuses on this detail and shows that it entails an as yet unnoticed connection with a core of biblically ingrained traditions that gain momentum in the Second Temple period and come to the fore afterwards in the works of ancient Jewish and Christian authors: traditions that equate God’s money with money intended for the poor. In order to substantiate my claim, I survey texts in Deuteronomy, Tobit, and the Epistle of Jeremiah in search of hints of this process of “pauperization” of God’s property, and proceed to investigate the history of reception of 2 Macc 3:10 in the Latin translations, among the church fathers, and in the post-Talmudic work Josippon. The aim is to demonstrate that 2 Macc 3:10 became a productive link in the rhetorical formulation of a topos which bore long-lasting literary, theological, and practical fruits.